2021
DOI: 10.1371/journal.pcbi.1009650
|View full text |Cite
|
Sign up to set email alerts
|

Graphical integrity issues in open access publications: Detection and patterns of proportional ink violations

Abstract: Academic graphs are essential for communicating complex scientific ideas and results. To ensure that these graphs truthfully reflect underlying data and relationships, visualization researchers have proposed several principles to guide the graph creation process. However, the extent of violations of these principles in academic publications is unknown. In this work, we develop a deep learning-based method to accurately measure violations of the proportional ink principle (AUC = 0.917), which states that the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…A recently developed automated screening tool identifies bar graphs in which the y-axis does not start at zero [ 23 ]. Our data highlight that it would be best to apply this tool only to bar graphs of counts or proportions.…”
Section: Discussionmentioning
confidence: 99%
“…A recently developed automated screening tool identifies bar graphs in which the y-axis does not start at zero [ 23 ]. Our data highlight that it would be best to apply this tool only to bar graphs of counts or proportions.…”
Section: Discussionmentioning
confidence: 99%
“…Technologies that can automatically examine figures in published scientific papers will benefit experts who need to accomplish such an important and difficult task. Zhuang et al analyzed graphical integrity issues in open access publications by verifying if the size of shaded areas in scientific figures were consistent with their corresponding quantities [186]. Moreira et al demonstrated a human-inthe-loop end-to-end scientific publication analysis process.…”
Section: Text and Document Forensicsmentioning
confidence: 99%
“…We argue, however, that insets can—and should—be used to support purposive communication. In scientific publications, an inset might be a diagram, image, graph, or plot that nudges the eye onto meaningful details or a supportive side story on top of the main message (Tufte 2006; Wainer 2005; Wang et al 2021; Zhuang, Huang, and Acuna 2021). 1…”
Section: Introductionmentioning
confidence: 99%
“…We argue, however, that insets can-and should-be used to support purposive communication. In scientific publications, an inset might be a diagram, image, graph, or plot that nudges the eye onto meaningful details or a supportive side story on top of the main message (Tufte 2006;Wainer 2005;Wang et al 2021;Zhuang, Huang, and Acuna 2021). 1 Inset plots, in particular, are most typically used to "zoom in" on data that are densely clustered, though they may also be used to view variable distributions, anomalies (without the effects of visual compression), or additional relevant data.…”
Section: Introductionmentioning
confidence: 99%